Randomised trial of continuous nasogastric, bolus nasogastric, and transpyloric feeding in infants of birth weight under 1400 g. Issue 4 (April 1992) - Macdonald, P D; Skeoch, C H; Carse, H; Dryburgh, F; Alroomi, L G; Galea, P; Gettinby, G
Abstract : Forty three infants under 1400 g were fed by a bolus nasogastric, continuous nasogastric, or transpyloric route. There were more complications with transpyloric feeding and no identifiable benefits in the growth rate, oral energy input, or chosen biochemical indices of nutrition. Bolus or continuous nasogastric feeds rather than transpyloric are better routine methods in infants of low birth weight.